Declining Discount Rate Estimate in the Long-Term Economic Evaluation of Environmental Projects - Nesticò, Antonio; Maselli, Gabriella (Journal of Environmental Accounting and Management, 2026)
The decision-making processes regarding projects with long-term environmental implications are strongly influenced by the estimate of the Social Discount Rate (SDR). An economic parameter that makes it possible to compare financially the Cash Flows (CFs) that occur at different time points, in the discounting the SDR reduces excessively the costs and benefits more distant over time. If this problem is particularly marked in the Cost-Benefit Analysis (CBA) conducted with time-invariant discount rates, it can be overcome by adopting time-declining discount rates. Thus, starting from the examination of the potentialities connected with the application of hyperbolic discounting in the CBAs, the aim of the work is to characterize an innovative probabilistic model for estimating the Declining Discount Rate (DDR), able to overcome the limits of the theoretical approaches recognized in the literature. The model is implemented on the data of the Italian economy and the DDRs estimated in this way are used in the economic feasibility study of an irrigation reconversion intervention. The processing proves that the adoption of time-declining discount rate allows attributing greater “weight” to the positive long-term externalities that characterize the interventions that promote sustainable development. This with decisive repercussions on the priority order of the initiatives to be financed and therefore on the entire allocation process of resources to be used to projects with intergenerational environmental implications. (*) The contribution to this paper is the result of the joint work of the two authors, to which the paper has to be attributed in equal parts.